COMPARISON OF INTERNAL JUGULAR VEIN WITH SUBCLAVIAN VEIN HEMODIALYSIS CATHETER ACCESS - Muhammad Khalid; Muhammad Akram Malik; Muhammad Imran bhatti et al. (Journal of University Medical & Dental College, 2017)
Abstract Objectives: To compare internal jugular vs. subclavian venous approach for the placement of central venous line for hemodialysis in term of complication. Material and methods: All Patients requiring placement of central venous catheter for dialysis, were included in this study, on random basis Patients were divided into two groups. One group of patients underwent internal jugular catheterization; and in 2nd group of patients subclavian catheterization was performed. Complications of catheter’s placement were recorded. Data was collected and analyzed by using SPSS 23. We applied chi-square test for qualitative data analysis. Results: Total 417 patients, were included in the study. In the patients who underwent internal jugular catheterization for central venous catheterization, 26 (12.3%) patients were reported to have arterial puncture as compared to 3 (1.44%) patients who have gone through subclavian approach. Malposition of the catheter tip of the subclavian catheterization 24 (11.59%) was significantly more than the internal jugular 4(1.9%).The incidence for blood stream infections with jugular access 12 (5.71%) was higher than subclavian access 8 (3.86 %).Thrombosis was reported in 23 (10.9%) patients with jugular catheterization in comparison with 5 (2.41 %) patients with subclavian cannulation.The differences in other complications on two approaches were statistically insignificant as occurrence of hemothorax was reported in 5 (2.41%) patients with subclavian catheterization compared to 3 (1.42%) patients with internal jugular approach. Incidence of hematoma was higher in jugular venous line 9 (4.28%) compared to subclavian approach 1 (0.48 %). Failure rate was significantly higher in cases with internal jugular vein catheter 20 (9.5%) compared to cases with subclavian vein catheter 4 (1.93%). Conclusion: Subclavian catheterization is more appropriate route for central venous catheter placement as it is associated with lower risk and increased chances of fast and safe recovery of the patients. Access time in subclavian catheterization is less as compared to internal jugular approach. This technique can be safely performed in centers where color Doppler ultrasound machine is not available in operation theatre complex.